Attitudes towards digital health tools for outpatient cirrhosis management in patients with decompensated cirrhosis. Issue 1 (14th January 2020) - Bloom, Patricia Pringle; Marx, Madeline; Wang, Thomas J; Green, Bradley; Ha, Jasmine; Bay, Camden; Chung, Raymond T; Richter, James M
Abstract : Background: Technology represents a promising tool to improve healthcare delivery for patients with cirrhosis. We sought to assess utilisation of technology and preferred features of a digital health management tool, in patients with an early readmission for decompensated cirrhosis. Methods: We conducted a cross-sectional study of patients readmitted within 90 days for decompensated cirrhosis. A semistructured interview obtained quantitative and qualitative data through open-ended questions. Results: Of the 50 participants, mean age was 57.6 years and mean (range) model for end stage liver disease was 22.7 (10–46). Thirty-eight (76%) patients own a Smartphone and 62% have regular access to a computer with internet. Thirty-nine (78%) patients would consider using a Smartphone application to manage their cirrhosis. Forty-six (92%) patients report having a principal caregiver, of which 80% own a Smartphone. Patients were interested in a Smartphone application that could communicate with their physician (85%), send medication notifications to the patient (65%) and caregiver (64%), transmit diagnostic results and appointment reminders (82%), educate about liver disease (79%), regularly transmit weight data to the doctor (85% with ascites) and play a game to detect cognitive decline (67% with encephalopathy). Common themes from qualitative data include a desire to learn about liver disease and communicate with providers via digital tools. Conclusion: Among patients with cirrhosis with an early readmission for decompensation, most have Smartphones and would be willing to use a Smartphone to manage their disease. Future digital health management tools should be tailored to the use patterns and preferences of the patients with cirrhosis and their caregivers.